Simple and safe heparin regimen for acute ischaemia - P. R. M. Bittencourt; S. Padilha; S. Mazer (Arquivos de Neuro-Psiquiatria)
The risk/benefit ratio of acute anticoagulation in ischaemic cerebro-vascular disease is not clearly established. A simple and safe intermittent intravenous heparin regimen (20000 IU daily) was used prospectively in 50 patients of 57 ± 14 (m ± sd) years of age whose blood pressures ranged from normal to severe hypertension. Twenty-two patients had cardiogenic embolism and the remaining had recurrent severe transient ischaemic attacks of recent onset or progressive cerebral infarcts. Time of exposure to heparin was 6.4 ± 4 (m±sd) days. Two patients had recurrences of cerebral thromboembolism and none had bleeding complications. This is a safe and efficient method of anticoagulation for patients with cerebral ischaemia when continuous infusion of heparin or close monitoring of clotting times are not used routinely.